How Will UMPSA Thrive Across Borders Yet Remain True to Its Roots? - Yatimah, Alias (UMPSA, 2025)
Last June, I shared my reflections on leadership, the kind of leadership rooted in values and purpose that we need as UMPSA moves through its transformation. Leadership, however, is not exercised in isolation. It must respond to the world around us.